Design Of Solar Street Light With Auto Intensity Control Using Arduino - Zahari, Nur Aisar; Yaacob, Megat Satria Zainuddin; Zainal, Mohd Shamian; Ahmad Lokman, Muhammad Faris Syauqi (Progress in Engineering Application and Technology, 2020)
The purpose of solar street light project is to design a system that do not consume huge amount of electricity, maintaining maximum utilization and minimum loss of energy. Solar is a non-conventional energy source and electricity can be captured by solar panel and stored into battery by using charge controller. The function of charge controller is to control the charging of the battery. This stored energy is used to glow the street lights during the whole night. Solar streetlight is designed based on microcontroller (Arduino Uno) as a controller to read the inputs of light on a sensor and turn it into an output. This project will be using two sensors which are LDR (light dependent resistor) sensor and IR (infra-red) sensor. LDR sensor is a light sensor which is used to measure intensity of light. Then IR sensor is a combination of infrared transmitter and receiver will use to detect the motion of vehicles, human, or anything that pass through it. Street light will switch ON at the dusk and switched OFF at the dawn automatically, emits low intensity light when there is no movement and emits high intensity lighting when it detect a movement of either vehicle or people passing through.